Heterotrigona itama workers bees homing ability as the basis for colony placement - RUSDIMANSYAH RUSDIMASNYAH; KHASRAD KHASRAD; JASWANDI JASWANDI; RUSFIDRA RUSFIDRA; DELLA AULIA (Society for Indonesian Biodiversity, 2024)
Abstract. Rusdimansyah R, Khasrad K, Jaswandi J, Rusfidra R, Aulia D. 2024. Heterotrigona itama workers bees homing ability as the basis for colony placement. Biodiversitas 25: 2478-2483. This study aimed to evaluate the ability of Heterotrigona itama worker bees to return to the nest from various test distances. This research is an observational study using the translocation method. There were 550 individuals of H. itama worker bees from 5 colonies reared for over two years. Each worker bee sample was identified with a mark in the form of water-based paint before being released at a testing distance every 100 meters until a distance where no more worker bees returned. The camera with a macro lens is installed at the entrance to the beehive to record worker bees returning to the hive. The video recording process was carried out over 90 minutes. The parameters observed included environmental temperature and humidity, the number of worker bees returning, and the time required for worker bees to return from each test distance. The data obtained were analyzed using Chi-square, Kruskal-Wallis, and Mann-Whitney U-test. The research showed that the maximum distance that H. itama worker bees can travel to return to the nest was 1000 meters. However, the most effective return distance was more than 500 meters because although some worker bees can return from greater distances, the number of returns significantly decreases after passing 500 meters. Therefore, the ideal distance for placing a colony of H. itama is less than 500 meters from the source of bee food plants. The minimum distance to move a colony from the initial location to a new location is around 1100 meters.